Multi-agent based simulation XVII : International Workshop, MABS 2016, Singapore, Singapore, May 10, 2016, Revised selected papers /: International Workshop, MABS 2016, Singapore, Singapore, May 10, 2016, Revised selected papers. (2017) - Unknown
No abstract available